Long-Term Sustainability of Outer Space Activities and Space Traffic Management - Olga Stelmakh-Drescher (Advanced Space Law, 2023)
This research addresses the critical importance of long-term sustainability and coordinated management of space traffic in the era of rapidly increasing space activities. It focuses on the necessity for globally coordinated action and robust legal frameworks to ensure operational, feasible, and enforceable space sustainability and traffic management strategies. The discussion highlights the environmental, ethical, and economic challenges posed by space debris and the proliferation of space activities. It also examines key initiatives and guidelines for space sustainability and traffic management, including the roles of space situational awareness (SSA) and the integration of SSA capabilities with effective space traffic management (STM). The presentation emphasizes the urgency of promoting environmentally responsible behaviors and sustainable practices in space activities, advocating for a future-focused approach that balances current needs with the preservation of outer space for future generations.